1995
DOI: 10.1021/jm00014a013
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sequestering Agents for the Actinides. 28. Synthesis and Initial Evaluation of Multidentate 4-Carbamoyl-3-hydroxy-1-methyl-2(1H)-pyridinone Ligands for in Vivo Plutonium(IV) Chelation

Abstract: A new family of chelating agents based on 4-(substituted-carbamoyl)-3-hydroxy-2-pyridinones is reported. These have optional terminal substituents on the nitrogens, and the hydroxypyridonate (HOPO) rings are attached to molecular backbones through amide linkages. A very important feature of the methyl-substituted ligand derivatives (Me-3,2-HOPOs) is that, similarly to the catechoylamide complexes of the siderophore enterobactin and its analogs, these HOPO derivatives form strong hydrogen bonds between the amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 89 publications
(146 citation statements)
references
References 17 publications
4
140
0
2
Order By: Relevance
“…32,33 The attachment of the CMPS moieties was facilitated using synthetic methodology developed for preparation of the hydroxypyridinones. 39 Since all steps of these syntheses are high yielded, multi-gram quantities of ligands were produced with little synthetic effort…”
Section: Synthesis Of Tris-cmpo and Tris-cmps Ligand Systemsmentioning
confidence: 99%
“…32,33 The attachment of the CMPS moieties was facilitated using synthetic methodology developed for preparation of the hydroxypyridinones. 39 Since all steps of these syntheses are high yielded, multi-gram quantities of ligands were produced with little synthetic effort…”
Section: Synthesis Of Tris-cmpo and Tris-cmps Ligand Systemsmentioning
confidence: 99%
“…Among those developed, the bidentate hydroxypyridinones, 3-hydroxy-4-(1H)-pyridinones (3,4-HOPOs), developed by Hider et al 5 have proven efficacy as Fe chelators. The 4-carboxy-3-hydroxy-1-methyl-2-(1H)-pyridinones (Me-3,2-HOPOs) developed in the laboratory of Dr. Kenneth Raymond 6 have potential efficacy as Fe chelators. When ionized, these HOPO isomers are isoelectronic with catechol, the bidentate functional group of hexadentate enterobactin, a powerful naturally produced Fe chelator.…”
Section: Introductionmentioning
confidence: 99%
“…7 10 and can be produced at a reasonable cost. 6,8,[10][11][12] Preclinical studies of the bidentate CP20 suggested a potency comparable to DFO when the 1:3 metal/chelator stoichiometry required to form the preferred hexacoordinated ferric complex was considered. 11 Clinical investigations of in vivo Fe chelation have been initiated with CP20, but bone marrow cytotoxicity, presumably associated with the large amounts of CP20 needed for effective Fe removal from the human, is a serious concern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations